Median Nerve-Neurophysiological Index Correlates With the Survival of Patients With Amyotrophic Lateral Sclerosis - Xu, Liu-Qing; Hu, Wei; Guo, Qi-Fu; Lai, Lu-Lu; Xu, Guo-Rong; Chen, Wan-Jin; Wang, Ning; Zhang, Qi-Jie (Frontiers in Neurology, 2020)
Objective: To explore the association between median nerve-neurophysiological index (NI) and survival of patients with amyotrophic lateral sclerosis (ALS). Methods: A retrospective case series with a prospective follow-up study was performed in 238 ALS patients. Their clinical profiles and NI were recorded. Kaplan-Meier curves and Cox regression were adopted to perform survival analysis. Results: The median survival time of all ALS cases was 33.0 months. Multivariate analysis showed that older age of onset, shorter diagnostic delay, higher ΔALSFRS-R, and faster progression (NI ≤2.15; hazard ratio [HR] = 1.543, 95% confidence interval [CI] 1.136-2.094) were associated with short survival. NI was correlated with ALSFRS-R at baseline (rs=0.3153, p<0.0001) and ALSFRS-R at different time points of follow-up (rs=0.5127, p<0.0001). The higher NI slope of decline (>0.25) showed shorter survival compared to the lower group (≤0.25) (34.0 months vs. 52.0 months, p=0.0003). A predictive model was constructed based on the age of onset, diagnostic delay, median nerve-NI, and ΔALSFRS-R. The higher predictive score (>14) showed significantly shorter survival compared to the lower group (≤14) (HR=3.907, 95%CI 2.857-5.342). Conclusion: Median nerve-NI and its slope of decline were predictive of survival of ALS.